(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2021)
The image of the country and its perception in the world is one of the most important directions in the politics of modern states. Modern Russia is a country with a controversial image, and today serious debates are raging around this issue in the scientific community. In this article, we will consider issues related to the perception of the image of Russia in the post-bipolar period. Russia, which has a rich history and geopolitical ambitions, is perceived ambiguously today, for some it is an aggressor country, a patron of undemocratic regimes, and for others it is a state that can challenge the hegemony of the United States. The modern image of the country is based on the basis that the Soviet Union formed. As Joseph Nye once noted, the image was associated with victory in World War II, space exploration, and achievements in sports. Modern attacks on Russia are connected with these issues, an active campaign is being conducted to reassess the results of the Second World War, monuments to Soviet soldiers are being demolished in Eastern Europe, their graves are being desecrated, Russia is being accused of using doping in sports, and the anthem was banned at the Olympic Games. Key words: Russia, Soft power, image, perception, propaganda, Crimea, Putin, regime.